Penerapan Praktek dan Teori Akuntansi Syariah sebagai Sistem Informasi - Muammar Khaddafi; Armidah Armidah; Ade Andriana Salsabila; Annisa Sagala; Icha Riani; Asnah Ritonga (STIKes Ibnu Sina Ajibarang, 2024)
Sharia accounting is an accounting system that is based on sharia principles that apply in Islamic law. The need for implementing sharia accounting has increased along with the development of the sharia economy in various countries, including Indonesia. The aim of this research is to identify and develop the application of sharia accounting practices and theories to make them more relevant to the needs of modern information systems. By utilizing a qualitative approach through literature studies, this research analyzes how sharia accounting concepts can be applied in effective and efficient information systems. The research results show that a sharia accounting-based information system needs to consider aspects of transparency, accountability and justice in accordance with sharia values. The implementation of technology in the sharia accounting information system is expected to strengthen reporting mechanisms that are more accurate and accessible to various related parties.